An Exploration of Non-Coding RNAs in Extracellular Vesicles Delivered by Swine Anterior Pituitary - Xiong, Jiali; Zhang, Haojie; Zeng, Bin; Liu, Jie; Luo, Junyi; Chen, Ting; Sun, Jiajie; Xi, Qianyun; Zhang, Yongliang (Frontiers in Genetics, 2021)
The anterior pituitary is a key endocrine organ in animals and humans. Extracellular vesicles are lipid bilayer-delimited particles carrying proteins, lipids, and small RNAs. Previous studies have demonstrated that they had regulatory functions both physiologically and pathologically. However, information on extracellular vesicles from the anterior pituitary remains unknown. In this study, we separated and identified extracellular vesicles from the anterior pituitary of the Duroc swine model for the first time. Total RNA was extracted and RNA-seq was performed, followed by a comprehensive analysis of miRNAs, lncRNAs and circRNAs. Resultantly, we obtained 416 miRNAs, 16232 lncRNAs, and 494 circRNAs. Furthermore, GO and KEGG enrichment analysis showed that the ncRNAs in extracellular vesicles may participate in regulating intracellular signal transduction, cellular component organization or biogenesis, small molecule binding, transferase activity. The cross-talk between them also suggested that they may play an important role in the signaling process and biological regulation. This work firstly provides ncRNAs data in anterior pituitary extracellular vesicles from the duroc swine breed. These results may serve as a fundamental resource for exploring the detailed functions of extracellular vesicles from the anterior pituitary.